KEPEMIMPINAN PEREMPUAN SEBAGAI KEPALA SEKOLAH - Raiyana Putri Kana; Eka Indriani; M. Joharis Lubis (Sekolah Tinggi Pariwisata Mataram, 2022)
Women's leadership as school principals in this scientific article aims to describe leadership styles, women, school principals that appear in decision making, building communication and providing motivation. The research method used is qualitative. The results of the research are the leadership of female school principals: (1) The principal gives authority to make decisions to subordinates; (2) Be careful in making decisions and adhere to procedures; (3) Respect, appreciate, be open to input and suggestions from subordinates; (4) Prefers to work in a team; (5) Prioritizing interpersonal relationships and informal communication; (6) awards are given for the development of subordinates; (7) motherhood plays a role in giving warnings and coaching to subordinates as well as being more diplomatic. (8) participatory leadership style